The Implementation of Self Regulated Learning Model Using Ict Media Toward The Students Achievement in Introduction to Accounting Course - Herawati, Nyoman Trisna (Universitas Negeri Malang, 2017)
This study aimed at describing an effect of implementing self regulated learning (SRL) models towards studentsâ achievement in Introduction to Accounting course. The study was conducted at the Department of Accounting in 2015/2016 utilizing a post-test only control group design, involving the second semester students as the subject. The Samples were determined based on simple random sampling in which every individual in the population had an equal chance to be chosen as a sample. The results of the post-test indicated that the students who were treated with self regulated learning (SRL) models had better achievement than those treated with a conventional model. The means score of the experimental group was 79.64 higher than that the control group which was only 69.39. It can be concluded that the studentsâ achievement of experimental group was better than the control group. The result of t-test indicated that the assumption of equal variance not assumed significance probability 2.479 and the significant level about 0.016 (two tail), meaning that significance less than 0.05. The null hypothesis was rejected and the alternative hypothesis was accepted. This conclude that there was a significant difference between the studentsâ achievement treated by self regulated learning (SRL) models and those treated with conventional models.Â Keywords: SRL, Media ICT, Learning Outcomes